POSTMODERN (UN)ENDINGS. THE SUBJECT AND INFINITY IN MODERN AND POSTMODERN LITERATURE (Filološke pripombe, 2019)
The paper explores the possible endings of narratives in the classical European novel from Cervantes through Goethe to Flaubert and the twentieth-century modernist novel of Proust, Kafka, Joyce, Beckett, and García Márquez. Against this background, the twenty-first-century novel The Pianist’s Touch [Pianistov dotik] by Mirt Komel is interpreted. The thesis is that the European novel has grown progressively incapable of bringing the story to a close: in Kafka, the castle is never to be reached, in Proust, the infinite Time itself incarnates, in Beckett, the flow of words never comes to an end, and in García Márquez, the ending is only a fulfillment of a prophecy in which we are eternally caught. It is the modernist collapse of the symbolic structure of the world that condemns the hero to this kind of “narrative infinity.” By contrast, in Komel’s novel the symbolic frame of reality has never existed, which is why the world no longer addresses, interpellates or obliges the protagonist, but rather lets him be apotheosized into a transcendent element in the midst of the immanence of the world.